2015
DOI: 10.1093/gbe/evv170
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Coevolution in the Bacterial Symbiosis of Whiteflies and Related Plant Sap-Feeding Insects

Abstract: Genomic decay is a common feature of intracellular bacteria that have entered into symbiosis with plant sap-feeding insects. This study of the whitefly Bemisia tabaci and two bacteria (Portiera aleyrodidarum and Hamiltonella defensa) cohoused in each host cell investigated whether the decay of Portiera metabolism genes is complemented by host and Hamiltonella genes, and compared the metabolic traits of the whitefly symbiosis with other sap-feeding insects (aphids, psyllids, and mealybugs). Parallel genomic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
274
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 162 publications
(291 citation statements)
references
References 61 publications
14
274
1
2
Order By: Relevance
“…In this study, we provide multiple lines of evidence to support the identified HGTs, including the alignments of paired-end and mate pair DNA reads and polyA-enriched strand-specific RNA-Seq reads (see Methods for details; Additional file 1: Figure S9; Additional files 17 and 18). In addition, our RNA-Seq data indicated that most of the HGTs were moderately or highly expressed, and 10 HGTs of bacterial origin were previously confirmed by qPCR [24]. Together, our data strongly support the high confidence of the identified HGTs in the B. tabaci genome.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…In this study, we provide multiple lines of evidence to support the identified HGTs, including the alignments of paired-end and mate pair DNA reads and polyA-enriched strand-specific RNA-Seq reads (see Methods for details; Additional file 1: Figure S9; Additional files 17 and 18). In addition, our RNA-Seq data indicated that most of the HGTs were moderately or highly expressed, and 10 HGTs of bacterial origin were previously confirmed by qPCR [24]. Together, our data strongly support the high confidence of the identified HGTs in the B. tabaci genome.…”
Section: Resultssupporting
confidence: 83%
“…Approximately 22% of the Rickettsia genes are homologous to transposable elements, suggesting that the genome is highly dynamic. Comparative analysis of the B. tabaci genome with the Portiera and Hamiltonella genomes identified genes coding for complementary reactions in multiple metabolic pathways, including essential amino acid biosynthesis (Additional file 1: Figure S8 and Additional file 16), as reported previously [24, 44]. Analysis of the Rickettsia genome also shows the absence of genes for non-essential amino acid biosynthesis (Additional file 1: Figure S8 and Additional file 16) .…”
Section: Resultssupporting
confidence: 67%
“…In each of these cases, no other bacterial genes or pseudogenes were found within the scaffolds (Tables S2 and S3), suggesting that these HGTs resulted from the transfer of small DNA fragments or that flanking bacterial DNA from larger fragments was lost after the transfer was established. The origin of some of these transfers [7,8-diaminopelargonic acid synthase and biotin synthase (bioAB)] likely predates the entire mealybug lineage, because they are found in the genome of the whitefly Bemisia tabaci (11).…”
Section: Phylogenetic Analyses Confirm the Intra-tremblaya γ-Proteobamentioning
confidence: 99%
“…For example, deep sea tube worms, some protists, and many sap-feeding insects are completely dependent on intracellular bacteria for essential nutrient provisioning (5)(6)(7). Some of these symbioses can form highly integrated organismal and genetic mosaics that, in many ways, resemble organelles (8)(9)(10)(11). Like organelles, these endosymbionts have genomes encoding few genes (12,13), rely on gene products of bacterial origin that are encoded on the host genome (9-11, 14, 15), and in some cases, import protein products encoded by these horizontally transferred genes back into the symbiont (16,17).…”
mentioning
confidence: 99%
See 1 more Smart Citation